Perception and Preventive Behaviour about COVID-19 Pandemic among the Members of a Selected Cantonment in Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Appropriate knowledge, attitude and practice against any infectious disease improve perception and consequently adopt preventive practices toward disease transmission. Good perception and preventive practice is the key to prevent infectious disease like COVID-19.Objective: To assess the perception and protective behaviour against COVID-19 among the members of Shaheed Salahuddin Cantonment, Ghatail.Materials and Methods: This cross-sectional study was conducted at Shaheed Salahuddin Cantonment from March 2022 to May 2022 among conveniently selected 1315 respondents. Data were collected through face-to-face interview using a pretested semi-structured questionnaire.Results: The majority (79.8%) of the respondents were male, residing in the sainik line (72.3%) having monthly income of